2009
DOI: 10.1007/s00256-009-0692-z
|View full text |Cite
|
Sign up to set email alerts
|

Is a single direct MR arthrography series in ABER position as accurate in detecting anteroinferior labroligamentous lesions as conventional MR arthography?

Abstract: Purpose The purpose of this study is to retrospectively compare accuracy of single magnetic resonance (MR) arthrography series in Abduction External Rotation (ABER) with conventional MR arthrography for detection and characterisation of anteroinferior labroligamentous lesions, with arthroscopy as reference standard. Interobserver variability of both protocols was determined. Methods and materials Institutional review board approval was obtained; informed consent was waived. MR arthrograms, including oblique ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 24 publications
0
32
0
10
Order By: Relevance
“…Given these indications of greater diagnostic accuracy, further study is therefore warranted to investigate the appropriateness of using higher field strength machines in the assessment of patients with suspected labral lesions. Six studies assessed the diagnostic test accuracy of MRI or MRA in abduction and external rotation shoulder positions (ABER) [21,24,[31][32][33][34]. It has been hypothesised that by positioning the patient's shoulder in this position, the anterior band of the inferior glenohumeral ligament is then placed under greater tension so that the anterior glenoid labrum is then distracted which optimises the penetration of contrast material into a tear [31].…”
Section: Discussionmentioning
confidence: 99%
“…Given these indications of greater diagnostic accuracy, further study is therefore warranted to investigate the appropriateness of using higher field strength machines in the assessment of patients with suspected labral lesions. Six studies assessed the diagnostic test accuracy of MRI or MRA in abduction and external rotation shoulder positions (ABER) [21,24,[31][32][33][34]. It has been hypothesised that by positioning the patient's shoulder in this position, the anterior band of the inferior glenohumeral ligament is then placed under greater tension so that the anterior glenoid labrum is then distracted which optimises the penetration of contrast material into a tear [31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that ABER has equal, if not better, sensitivity and specificity compared to standard MR arthrogram views for detecting anterior inferior labroligamentous lesions. 23 Hence, our findings indicate once more that reestablishment on MR arthrogram at 6 months postoperatively may not correlate with functional outcomes.…”
Section: Discussionmentioning
confidence: 79%
“…A typical example is presented in [16]. From the comparison of an imaging method (conventional magnetic resonance, MR) in n = 92 patients to the gold standard (arthroscopy, AR) in detection of supraspinatus tendon tears, the numbers in Table 1 resulted.…”
Section: Compare Paired Proportionsmentioning
confidence: 99%
“…The main scientific question in [16] was to evaluate sensitivity and specificity of MR and a second experimental method, abduction external rotation (ABER), see Table 3 for the corresponding number of patients. The two experimental methods, MR and ABER, differ in the positioning of the patient's arm.…”
Section: Compare Sensitivity and Specificity Between Groupsmentioning
confidence: 99%
See 1 more Smart Citation